ANALISIS PERBANDINGAN PENDAPATAN USAHA GULA MERAH DENGAN USAHA GULA TAPO (STUDI KASUS DI DESA AMBESIA KACAMATAN TOMINI KABUPATEN PARIGI MOUTONG) - Nirmalasari, Firsta Olyvia; Mappatoba, Marhawati; Alam, Max Nur (AGROTEKBIS, 2013)
This study attempted to determine the revenues of brown sugar and tapo sugar and to investigate the difference between these two revenues. A census sampling method for sugar producers was done, collected 30 respondents i.e 15 respondents for brown sugar producers and others 15 for Tapo Sugar. The hypothesis was that the revenue obtained from brown sugar was lesser than tapo sugar. The result showed that the average revenue from brown sugar is 498,449 IDR per month and Tapo is 2,437,639 IDR per month, t-test showed the t value is -6.982 with critical t value 2.048 which indicates that t value > critical t value, means there is a significant difference between the revenue of brown sugar with tapo Sugar in the Ambesia village, district Tomini Moutong Parigi region.